Animal Cancer Research - Sahoo, Aditya P.; Somvanshi, R.; Sonal, Sonal; Kumar, G. Ravi; Kumar, Pawan; Tiwari, Ashok K. (Indian Farming, 2015)
In spite of all the advances made recently in human cancer therapeutics, adequate therapeutic approaches are still lacking for managing the animal cancer patients. Therefore, research initiated by IVRI in the field of animal cancer vaccines, gene therapy and diagnostics may provide a ray of hope for the future.